A semi-analytical one-dimensional model for offshore pile foundations considering effects of pile diameter and aspect ratio. (15th April 2022) - Wang, Lilin; Ishihara, Takeshi
Abstract: A semi-analytical 1D model with the eight types of soil reactions is derived from the fishbone frame model for pile foundations of wind turbines, in which the coupling between axial and lateral resistances that matters for large pile diameters and small pile aspect ratios is modeled as the rotational soil reactions. The only correction factor for the calculation of the ultimate bearing capacities of the lateral and rotational soil reactions on the pile shaft is then identified by a curve-fitting approach and validated using a series of experiments and 3D FE analyses for both sand and clay. The proposed model shows favorable agreements with the experiments and 3D FE analyses in terms of the load-displacement curves at the ground level and the rotation and moment responses for the pile foundations with various pile diameters and aspect ratios. Finally, the proposed model is further verified by monopiles in layered soils and applied to investigate the effect of the coupling between axial and lateral resistances on the modal damping of monopile supported wind turbines. Without considering the coupling between axial and lateral resistances, the modal damping ratios for the monopile supported wind turbine are underestimated significantly. Highlights: 1. A semi-analytical 1D model with the eight types of soil reactions is derived from the fishbone frame model, in which the coupling between axial and lateral resistances that matters for large pile diameters and small pile aspect ratios is modeled as the rotational soil reactions. 2. The proposed model shows favorable agreements with the experiments with various pile diameters and pile aspect ratios. However, the API model only suits the foundation with a small pile diameter and a large pile aspect ratio. 3. Without considering the coupling between axial and lateral resistances, the modal damping ratios for the monopile supported wind turbine are underestimated significantly.